Effect of Postoperative Analgesic Exposure to the Cannabinoid Receptor Agonist WIN55 on Osteogenic Differentiation and Spinal Fusion in Rats. (2nd June 2021) - Yun, Chawon; Haleem, Meraaj S.; Jeong, Soyeon; Oyer, Mark A.; Driscoll, Adam J.; Chang, Kevin Y.; Yun, Jonghwa; Paul, Jonathan; Lubbe, Ryan J.; Stock, Stuart R.; Hsu, Wellington K.; Hsu, Erin L.
Abstract : Background: After spinal surgery and other orthopaedic procedures, most patients receive opioids for pain, leading to potential complications such as pseudarthrosis and opioid abuse associated with long-term use. As an alternative, the endocannabinoid system has been shown to have antinociceptive activity, while contributing to bone homeostasis via the CB1 and CB2 cannabinoid receptors. This study evaluates the impact of the cannabinoid receptor agonist WIN55, 212-2 (WIN55) on osteogenic differentiation in vitro as well as bone regeneration and spinal fusion in a preclinical rat model. Methods: Primary rat bone marrow stromal cells were cultured in standard or osteogenic media and exposed to vehicle alone or WIN55. Runx2 and Alkaline phosphatase (Alpl) were quantified via qPCR (quantitative real-time polymerase chain reaction), followed by assessment of ALP activity and matrix mineralization. For in vivo evaluation, 45 female Sprague Dawley rats (n = 15 per group) underwent L4-L5 posterolateral spinal fusion with bilateral placement of collagen scaffolds preloaded with low-dose rhBMP-2 (recombinant human bone morphogenetic protein-2; 0.5 μg/implant). Postoperatively, rats received the vehicle alone or 0.5 or 2.5 mg/kg WIN55 via daily intraperitoneal injections for 5 days. Bone regeneration and spinal fusion were assessed using radiography, manual palpation-based fusion scoring, microcomputed tomography imaging, and histology. Results: mRNA expression levels of Runx2 and Alp were similar among cells treated with vehicle alone and WIN55. Likewise, exposure to WIN55 did not inhibit ALP activity or bone matrix mineralization. In this animal model, no significant differences were found among groups with regard to mean fusion score, fusion rate, or new bone volume. Conclusions: WIN55 showed no adverse impact on osteogenic differentiation, bone regeneration, and spinal fusion. This supports that cannabinoid receptor agonists should be further investigated as a potential alternative approach for postoperative analgesia following spinal fusion and other orthopaedic procedures requiring bone-healing. Clinical Relevance: The identification of alternative treatments for postoperative pain following orthopaedic surgical procedures is crucial in combating the ongoing opioid abuse crisis. The endocannabinoid system may represent a viable alternative target for addressing orthopaedic postoperative pain.